2018
DOI: 10.1111/ger.12349
|View full text |Cite
|
Sign up to set email alerts
|

Masticatory efficiency contributing to the improved dynamic postural balance: A cross‐sectional study

Abstract: With some reservations about statistical power, the association found between masticatory efficiency and postural balance justifies further investigations to confirm the strength of the associations, and possibly to identify causal relationships between mastication and posture in old age.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 9 publications
(9 citation statements)
references
References 21 publications
0
9
0
Order By: Relevance
“…Furthermore, the decrease in masticatory function with aging leads to decreased sensory input of the nervous system and cerebral blood flow [5,41], which may result in systemic deteriorations of elderly patients. In a study by Hwang et al [28], the dynamic balance of elderly participants with low masticatory efficiency was lower than that of elderly participants with high masticatory efficiency, which may lead to an increased fall risk. Bae and Park [42] reported that denture-wearers had decreased neck muscle strength than those without dentures, which may cause the body to bend forward.…”
Section: Discussionmentioning
confidence: 97%
See 2 more Smart Citations
“…Furthermore, the decrease in masticatory function with aging leads to decreased sensory input of the nervous system and cerebral blood flow [5,41], which may result in systemic deteriorations of elderly patients. In a study by Hwang et al [28], the dynamic balance of elderly participants with low masticatory efficiency was lower than that of elderly participants with high masticatory efficiency, which may lead to an increased fall risk. Bae and Park [42] reported that denture-wearers had decreased neck muscle strength than those without dentures, which may cause the body to bend forward.…”
Section: Discussionmentioning
confidence: 97%
“…A wax cube was masticated 10 times, and the total area of the wax specimen, the level of puncture, and the level of color mix were comprehensively evaluated to determine the MAI [15]. The wax cube was made by arranging red and green utility wax rods (Daedong Industrial Co., Ltd., Daegu, Korea) without any overlap in a 12 × 12 × 12 mm cube (Figure 1A) [28]. The participants were asked to masticate one wax cube with their right teeth 10 times, and the procedure was repeated with their left teeth (Figure 1B).…”
Section: Assessment Of Masticatory Performancementioning
confidence: 99%
See 1 more Smart Citation
“…Masticatory performance was assessed using the MAI, which is calculated by comprehensively evaluating the total area, degree of perforation, and degree of color mixing after masticating a wax cube. The wax cube, composed of red and green utility wax rods arranged as 12 mm × 12 mm × 12 mm (Daedong Industrial Co., Ltd., Daegu, Republic of Korea) without overlap [ 26 ], was masticated 10 times ( Figure 1 ). One cube was used for each side of the mouth.…”
Section: Methodsmentioning
confidence: 99%
“…Postural balance can be improved by performing the act of chewing [ 5 ]. In addition, chewing habit is correlated with forward head posture (FHP) [ 6 ], and a good oral health retains masticatory efficiency and postural muscular function (leading to good balance) in older adults [ 7 , 8 , 9 ]. Hence, tooth loss is a risk factor for postural imbalance [ 10 ], and dental occlusion is associated with static and dynamic balance [ 10 , 11 ].…”
Section: Introductionmentioning
confidence: 99%